Investigation on the Effect of Antibiotic and Multivitamin in the Formation of Biofilm in Urinary Tract Infection (UTI) Causing Pathogens - P Sajna, K; Paulraj, P; Balasupramaniam, V; Sajeesh, P; Chandramohan, M; Ketharin, T (International Journal of Engineering and Technology, 2019)
Urinary catheters make humans vulnerable to Urinary Tract Infection (UTI) by damaging the natural barrier of the body. Bacteria which are commonly related to this infection are Escherichia coli, Klebsiella pneumoniae and Pseudomonas aeruginosa. In this study Klebsiella pneumoniae and Pseudomonas aeruginosa were obtained from the hospital. Levofloxacin is a newly developed fluoroquinolone antibiotic, which is commonly used in clinical practice. The antibacterial effect of levofloxacin was studied using disk diffusion method. In this method the diameter of zone of inhibition in the presence of multivitamin was smaller than without multivitamin. The statistical analysis showed a significant difference in antibiotic sensitivity with and without multivitamin (p<0.05). In the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC), It was observed that in the absence of multivitamin Klebsiella pneumoniae growth stopped at the concentration of 200 µg/ml and in the presence of multivitamin the growth stopped at the concentration of 400 µg/ml. The growth of Pseudomonas aeruginosa stopped at the concentration of 400 µg/ml in the absence of multivitamin and in the presence the growth was stopped at the concentration of 800 µg/ml. Similar effect was studied in biofilm form as well by measuring the absorbance at 600nm. Using the absorbance values the biofilm growth curve was carried out and in the presence of multivitamin, both bacteria in single and consortia form stayed in stationary phase longer than without multivitamin. These findings demonstrate that a higher concentration of antibiotic is required to inhibit the growth of bacteria when supplemented with multivitamins and in turn increases the development of antibiotic resistance under biofilm condition.